Socialism is great a worker's memoir of the new China - Zhang, Lijia (New York Anchor Books, 2009)
With a great charm and spirit, ?Socialism Is Great!? recounts Lijia Zhang's rebellious journey from disillusioned factory worker to organizer in support of the Tiananmen Square demonstrators, to eventually become the writer and journalist she always determined to be. Her memoir is like a brilliant miniature illuminating the sweeping historical forces at work in China after the Cultural Revolution as the country moved from one of stark repression to a vibrant, capitalist economy.
Originally published in hardcover in the United States by Atlas & Co. Publishers, New York, in 2008--T.p. verso.
Keywords: Zhang, Lijia, 1964-